Associations between lifestyle and comorbid anxiety and depression in pregnant women - Jiaqi ZHENG; Liyao HUANG; Yan ZHANG; Mengbi SHEN; Xiaojin WANG; Hong LI; Zhiwei LIU; Ying TIAN; Xiaoning LEI; Yu GAO (环境与职业医学, 2024)
BackgroundAnxiety and depression are common perinatal mental health issues that often occur together and can have serious negative effects on both maternal and infant health. ObjectiveTo examine the relationships between lifestyle factors and comorbid anxiety and depression (CAD) among pregnant women in Shanghai. MethodsThe study estimated the prevalence of CAD during the first, second, and third trimesters of pregnancy using the Self-rating Anxiety Scale (SAS) and Center for Epidemiological Studies-Depression (CES-D) based on data from the China National Birth Cohort (CNBC) embryonic-derived diseases with assisted reproductive technology (ART) sub-cohort. Information on demographics, sleep status, nutritional intake, and exercise during each trimester was collected through self-made questionnaires, the Pittsburgh Sleep Quality Index (PSQI), and the Food Frequency Questionnaire (FFQ). Lifestyle factors (such as sleep status, nutritional intake, and exercise during each trimester) were analyzed using logistic regression and generalized linear mixed models (GLMM) to determine their impacts on the prevalence of CAD (yes or no) among pregnant women. ResultsA total of 2876 pregnant women were included in this study. The prevalence of CAD was 10.6% (305), 3.6% (103), and 5.5% (159) in the first, second, and third trimesters of pregnancy, respectively. The logistic regression analysis revealed that poor sleep quality throughout the entire pregnancy were statistically associated with an increased prevalence of CAD, and the odds ratios (OR) with 95% confidence intervals (CI) were 2.817 (1.845, 4.301), 2.840 (1.855, 4.347), and 9.316 (5.835, 14.876) for the first, second, and third trimesters, respectively, when compared to good sleep quality. Additionally, compared to an intake frequency of 7 times per week, the frequency of egg intake ≤3 times per week in the first trimester (OR=2.025, 95%CI: 1.197, 3.425) and the frequency of egg intake of 4–6 times per week (OR=1.896, 95%CI: 1.117, 3.216) or ≤3 times per week (OR=1.906, 95%CI: 1.082, 3.357) in the third trimester were associated with an increased risk of CAD (P<0.05). Moreover, when compared to a frequency of exercise >3 times per week, never or almost never exercising in the second trimester (OR=2.218, 95%CI: 1.220, 4.035) was associated with an increased risk of CAD (P<0.05). The GLMM analysis also demonstrated a significant association between poor sleep quality, lower exercise frequency, or lower intake frequency of vegetables, eggs, or milk and an increased risk of CAD (P<0.05). ConclusionThe prevalence of CAD among pregnant women in Shanghai follows a U-shaped distribution, with the highest rate occurring in early pregnancy and the lowest rate in mid-pregnancy. Factors such as poor sleep quality, inadequate intake of vegetables, eggs, or milk, and lack of exercise during pregnancy may increase the risk of CAD. Implementing lifestyle interventions during pregnancy could potentially reduce the risk of mental health problems and improve the overall health of both mothers and babies.